1981
DOI: 10.1111/j.1365-2125.1981.tb01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium valproate and cognitive functioning in normal volunteers.

Abstract: 1 The effects ofsodium valproate on the performance ofa series ofpsychological tests and mood was studied. 2 Ten healthy male volunteers received sodium valproate and placebo, each for a period of2 weeks, in a double-blind cross-over design. Dosage of sodium valproate was increased to 800 mg/day in the first week and to 1 g/day in the second week of treatment. 3 Psychological testing took place on three occasions, before and on completion of each of the two treatment periods. 4 The few significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
4

Year Published

1986
1986
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 12 publications
5
26
0
4
Order By: Relevance
“…The day 3 comparison with placebo suggests that VPA alone has no important acute effect on psychomotor function. This is in general agreement with previous studies which have reported, at worst, only isolated decrements in cognitive function with the drug (Harding & Pullan, 1977;Sommerbeck etal., 1977;Thompson & Trimble, 1981). VPA treatment had a minor effect on the objective psychomotor test profile of CBZ.…”
Section: Analysesmentioning
confidence: 95%
“…The day 3 comparison with placebo suggests that VPA alone has no important acute effect on psychomotor function. This is in general agreement with previous studies which have reported, at worst, only isolated decrements in cognitive function with the drug (Harding & Pullan, 1977;Sommerbeck etal., 1977;Thompson & Trimble, 1981). VPA treatment had a minor effect on the objective psychomotor test profile of CBZ.…”
Section: Analysesmentioning
confidence: 95%
“…37 The card was removed and the athlete asked to recall the words. The score was the number correctly recalled.…”
Section: Immediate Word Recall (Iwr)mentioning
confidence: 99%
“…Тем не менее, в отдельных исследованиях было показано отрица-тельное влияние вальпроата (по выраженности -от легкого до умеренного) на скорость психомоторных реакций и скорость мыслительных процессов [28,29,38,66,81].…”
Section: старые антиэпилептические препаратыunclassified